Modification of the existing maximum residue levels for fenpyrazamine in lettuces, salad plants, spinaches and similar leaves. (3rd April 2018) - ; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Ferreira, Lucien; Greco, Luna; Janossy, Judit; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Sumitomo Chemical Agro Europe S.A.S. submitted a request to the competent national authority in France, to modify the existing maximum residue levels (MRLs) for the active substance fenpyrazamine in lamb's lettuces, lettuces, escaroles, dandelions, cresses, land cresses, rucola, red mustards, spinaches, purslanes and chards/beet leaves. The data submitted in support of the request were found to be sufficient to derive MRL proposals for lamb's lettuces/corn salads, lettuces, escaroles/broad‐leaved endives (including dandelions), cresses, land cresses, roman rocket/rucola, red mustards, spinaches, purslanes and chards/beet leaves. Adequate analytical methods for enforcement are available to control the residues of fenpyrazamine in the crops assessed in this application according to the enforcement residue definition. The methods enable quantification of residues in the crops assessed at or above 0.01 mg/kg (limit of quantification (LOQ)). Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of fenpyrazamine on lamb's lettuces/corn salads, lettuces, cresses, land cresses, roman rocket/rucola, red mustards, spinaches, purslanes and chards/beet leaves according to the reported agricultural practice is unlikely to present a risk to consumer health. According to the internationally agreed methodology for short‐term exposure estimation (IESTI), the acute reference dose (ARfD) was not exceeded for the intended use of fenpyrazamine on escaroles (97.6%), and thus, there is a narrow safety margin.